Fluid–structure interaction analysis of a healthy aortic valve and its surrounding haemodynamics - Yin, Zhongjie; Armour, Chlöe; Kandail, Harkamaljot; O'Regan, Declan P.; Bahrami, Toufan; Mirsadraee, Saeed; Pirola, Selene; Xu, Xiao Yun (International journal for numerical methods in biomedical engineering, 2024)
The opening and closing dynamics of the aortic valve (AV) has a strong influence on haemodynamics in the aortic root, and both play a pivotal role in maintaining normal physiological functions of the valve. The aim of this study was to establish a subject‐specific fluid–structure interaction (FSI) workflow capable of simulating the motion of a tricuspid healthy valve and the surrounding haemodynamics under physiologically realistic conditions. A subject‐specific aortic root was reconstructed from magnetic resonance (MR) images acquired from a healthy volunteer, whilst the valve leaflets were built using a parametric model fitted to the subject‐specific aortic root geometry. The material behaviour of the leaflets was described using the isotropic hyperelastic Ogden model, and subject‐specific boundary conditions were derived from 4D‐flow MR imaging (4D‐MRI). Strongly coupled FSI simulations were performed using a finite volume‐based boundary conforming method implemented in FlowVision. Our FSI model was able to simulate the opening and closing of the AV throughout the entire cardiac cycle. Comparisons of simulation results with 4D‐MRI showed a good agreement in key haemodynamic parameters, with stroke volume differing by 7.5% and the maximum jet velocity differing by less than 1%. Detailed analysis of wall shear stress (WSS) on the leaflets revealed much higher WSS on the ventricular side than the aortic side and different spatial patterns amongst the three leaflets. This study established a subject‐specific fluid–structure interaction (FSI) workflow capable of simulating the motion of a tricuspid healthy valve and the surrounding haemodynamics under physiologically realistic conditions. Comparisons of simulation results with 4D‐MRI showed a good agreement in key haemodynamic parameters. Detailed analysis of wall shear stress (WSS) on the leaflets revealed much higher WSS on the ventricular side than the aortic side and different spatial patterns amongst the three leaflets.